De Hiroshima aux Twin Towers : les désignants d’événements, une mémoire de l’actualité ? - Laura Calabrese Steimberg (Itinéraires)
This paper analyzes the ways in which event names in the media help to build historic memory. We will observe the behavior of media event-names in the press (The swine flu, 9/11), which help us to identify and trace events synthetically. From a discourse perspective, we raise the question of the marks at the surface of the text that allow us to interpret those expressions as events. Our hypothesis is that they first arise as noun phrases including an event noun (i.e. the 9/11 terror attacks), but the latter is gradually erased, as media discourse tends to produce synthetic expressions. We would like to show how those expressions organize collective memory, by stocking a great amount of information, by creating periods (post 9/11), comparisons by antonomasia (the Italian 9/11) or series of events (From Hiroshima to 9/11). Those examples show that event names organize historic memory by marking the rhythm of social life.